Analisis Sistem Pengendalian Intern, Siklus Pendapatan Untuk Keberlanjutan Perusahaan - Merida; Anggun Yuliana, Khrisna; Pratama, Ardiansyah (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To know and analyze the internal control system, Revenue Cycle for Company Sustainability, by Testing Internal Control System Variables, Income on Company Sustainability. Background Problems: The current development of globalization has caused business competition between companies to become increasingly stringent in achieving the principles of efficiency, effectiveness and economy. Novelty: Retesting variables at different companies with different methods. Research Methods: A sample of 34 respondents was taken, with the analytical tool used, namely SPSS. Finding/Results: This study shows that the Internal Control System variable has a positive and significant effect on Company Sustainability and the Revenue Cycle has no positive and insignificant effect on Company Sustainability. Conclusion: The internal control system and corporate cycle of the companies analyzed have very good corporate sustainability.